Investigation of the effectiveness of antibacterial prophylaxis in renal transplant recipients - Abdulmalik M Alkatheri; Abdulkareem M Albekairy; Shemylan Alharbi; Saleh N. Aldekhael; Nabil Khalidi; Abdullah A. Alsayyari; Wesam S. Abdel-Razaq; Amjad M Qandil (Journal of Infection in Developing Countries)
Introduction: Bacterial urinary tract infections (UTIs) are very common complications in renal transplant recipients (RTRs). Methodology: This study is a follow-up to a previous investigation of post-renal transplant UTIs, which led to changes in the antibacterial agents used for prophylaxis and its duration. In this retrospective study of the medical records of 86 RTRs, the incidence, risk factors, causative bacteria, and duration prophylaxis were investigated. Results: The average age of the RTRs was 41.55 ± 14.06 years, and two-thirds of them were males. A total of 57.3% of the RTRs received cadaveric kidneys; the rest received kidneys from living related donors. The prescribed regimen (one month or three months of co-trimoxazole and norfloxacin) was completed by 75% of the RTRs. The incidence of UTIs in the RTRs who received this prophylaxis was 32.3%, which was significantly lower than the incidence with norfloxacin alone (56%). Female gender was found to be a risk factor for post-renal transplant UTIs. Escherichia coli was the most common pathogen (51.7%), followed by Klebsiella and Enterobacter (17.2% each). Most UTIs (86.2%) were detected within the first post-transplant month. Conclusions: There was no clear advantage to prescribing antibacterial prophylaxis for three months versus one month, as 86.2% of the UTIs occurred within the first month post-transplant regardless of prophylaxis duration. Using co-trimoxazole/norfloxacin compared to norfloxacin alone did positively affect patient outcome by reducing the incidence of UTIs. This study recommends antimicrobial sensitivity-guided modification of the antibacterial agents used for prophylaxis rather than extension of its duration.